2010
DOI: 10.1128/jvi.01115-10
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of an Influenza Virus RNA Polymerase-Genomic RNA Complex

Abstract: The replication and transcription of influenza A virus are carried out by ribonucleoproteins (RNPs) containing each genomic RNA segment associated with nucleoprotein monomers and the heterotrimeric polymerase complex. These RNPs are responsible for virus transcription and replication in the infected cell nucleus. Here we have expressed, purified, and analyzed, structurally and functionally, for the first time, polymerase-RNA template complexes obtained after replication in vivo. These complexes were generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…3). 34,[60][61][62] These studies documented that the polymerase has a quite compact structure and is probably a flexible complex. Thus, comparing the isolated heterotrimeric complex with the RNP-bound or template-bound complexes indicates that the polymerase shows considerable conformational changes upon interaction with other viral (and presumably also cellular) partners.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 2 more Smart Citations
“…3). 34,[60][61][62] These studies documented that the polymerase has a quite compact structure and is probably a flexible complex. Thus, comparing the isolated heterotrimeric complex with the RNP-bound or template-bound complexes indicates that the polymerase shows considerable conformational changes upon interaction with other viral (and presumably also cellular) partners.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Although early in vitro studies indicated that the polymerase complex dissociates from the cap-structure soon after cap-snatching, 81 no in vivo studies have 62 the polymerase complex present in the recombinant RNP (middle, yellow), 34 and a polymerase-vRNA complex (bottom, blue). 61 …”
Section: To Switch or Not To Switchmentioning
confidence: 99%
See 1 more Smart Citation
“…Several different 3D conformations have been observed using cryo-and negative staining electron microscopy for the purified recombinant influenza viral polymerases in the presence or absence of vRNA, NP, and both [64][65][66][67]. Those studies demonstrated that the polymerase has a globular hollow conformation that becomes compacted upon association with vRNA alone or vRNA in the presence of NP oligomers [64][65][66][67].…”
Section: The Engine Behind a Pathogenic Machinery: Nuclear Accumulatimentioning
confidence: 99%
“…Those studies demonstrated that the polymerase has a globular hollow conformation that becomes compacted upon association with vRNA alone or vRNA in the presence of NP oligomers [64][65][66][67]. Additionally, PB1, PB2, and NP have been identified as the main viral proteins mediating the RNA-dependent interaction of the viral polymerase and the RNA-protein complex formed between NP and vRNA [65].…”
Section: The Engine Behind a Pathogenic Machinery: Nuclear Accumulatimentioning
confidence: 99%